The Preservation of the Arabic-Malay Script as A Reconstruction of the Existence of Malay Culture in Brunei Darussalam - Putra, Johan Septian (STAIN Sultan Abdurrahman Kepulauan Riau, 2025)
In the era of globalization in Brunei Darussalam, Islam and Malay culture continue to play a significant role in shaping the nation's identity. This role manifests in efforts to preserve the Islamic-Malay identity. The contemporary issue at hand concerns the degradation of local culture due to the penetration of foreign cultures, which has resulted in the erosion, and in some cases the loss, of indigenous cultural traditions. This article specifically examines the implementation of the Arabic-Malay script as a strategy to address the challenges posed by cultural penetration in the era of globalization, particularly during the reign of Sultan Hassanal Bolkiah in Brunei Darussalam. The method employed in this study is the historical research method, four stages: heuristics, source criticism, interpretation, and explanation, which is the process of presenting the findings in writing. The findings of research, they are: First, the independence of Brunei Darussalam and its declaration as a Malay Islamic Monarchy (Melayu Islam Beraja) was not solely the will of the king, but also the will of the people of Brunei as a whole. Brunei Darussalam continues to uphold its cultural heritage under the leadership of Sultan Hassanal Bolkiah in the contemporary era. The second, research on these manuscripts serves as a preventive measure to protect local culture from foreign influences that might enter Brunei Darussalam due to globalization. Last, the educational and research initiatives are serious steps taken by the Sultanate government during Sultan Hassanal Bolkiah's reign to ensure that Malay culture remains present and adaptable in any situation or condition